Comparison of Fibrosis-4 with FibroScan for Liver Fibrosis Assessment in Non-Alcoholic Fatty Liver Disease Patients: A Cross-sectional Study - Fahad kakar; Arif Rasheed Siddiqui; Saad Khalid Niaz; Syed Afzal ul Haq Haqqi; Zea ul Islam Farrukh; Muhammad Danish Ashraf Wallam; Muhammad Umar Farooq; Sayed Rohail Ahmed Rizvi (Journal of the Dow University of Health Sciences, 2024)
Objective: To identify the relationship between injection needle threat as a mode of disciplining children and acquired dental phobia in pediatric patients. Methods: This cross-sectional study was conducted at University College of Dentistry, Lahore, Pakistan between December 2021 and November 2022. The study included individuals under the age of 18 years who were presented during the survey and scheduled for pulpotomy or pulpectomy treatment. The study assessed two primary outcomes: dental anxiety and childhood needle threat. Dental anxiety was evaluated using the Modified Children's Dental Anxiety Scale, while childhood needle threat was measured by observing the child's responses to scenarios involving needles. Results: Of total 200 pediatric patients, the mean age was 12.04 ±2.34 years. Mild dental anxiety level was observed in 56 (28.0%) patients, moderate in 122 (61.0%) patients and severe in 22 (11.0%) patients. Childhood needle threat was observed in 94 (47.0%) patients. Patients with mild dental anxiety were 0.86 times significantly less likely to have needle threat as compared to patients with severe dental anxiety (cOR 0.14, 95% CI 0.04 to 0.48, p-value 0.002). Similarly, patients with moderate dental anxiety were 0.83 times significantly less likely to have needle threat as compared to patients with severe dental anxiety (cOR 0.17, 95% CI 0.05 to 0.55, p-value 0.003). Conclusion: The study revealed that most children exhibited moderate dental anxiety, with a notable incidence of dental phobia. Those with higher anxiety levels felt more threatened by needles, underscoring the need to avoid using needles as a mode of discipline.